Monitoring regional soil organic matter content using a spatiotemporal model with time-series synthetic Landsat images - Zhang, Mei-Wei; Wang, Xiao-Qing; Ding, Xiao-Gang; Yang, Hua-Lei; Guo, Qian; Zeng, Ling-Tao; Cui, Yu-Pei; Sun, Xiao-Lin (Geoderma Regional, 2023)
Accurately monitoring soil organic matter (SOM) content is crucial for food and soil security. Current methods of monitoring are expensive and existing sparse data cannot provide detailed spatial information about SOM content changes in an area. This study proposes using a spatiotemporal model with time-series synthetic Landsat images to monitor SOM content dynamics at the regional scale. The approach was implemented in Google Earth Engine (GEE) platform and tested in Jiangsu province, China, using the soil survey data from 2006 to 2007 and synthetic Landsat images from 1986 to 2007. The model generated SOM maps every three years between 1986 and 2007 and was evaluated using another soil survey from 2000 in southern Jiangsu. The model associated with 20 covariates derived from the synthetic Landsat image explained 70% of the variation in SOM content with root mean squared error (RMSE) and Lin's concordance correlation coefficient (CCC) of 5.17 g/kg and 0.57, respectively. The results showed that the model could reveal regional spatial and temporal differences in SOM content distribution. The SOM content in Jiangsu increased in the north, while decreasing in the central and southern areas. Temporally, the mean SOM contents increased from 1986 to 1992 by 0.17 g/kg, decreased in 1995, and increased again from 1998 to 2000 before decreasing from 2004 to 2007 by 0.14 g/kg. The validation based on the soil data in 2000 showed that the approach generated an RMSE of 5.97 g/kg, accounting for 22.77% of the average SOM content of the data. The study concluded that this approach could be used for monitoring SOM content and other soil properties. This approach had a relatively better accuracy than a previous study using the Integrated Nested Laplace Approximation with the Stochastic Partial Differential Equation approach with the same soil data but 4 times more samples. [Display omitted] •Time-series synthetic Landsat images of 1986–2007 were established based on GEE.•The image of 2005–2007 was used to fit a spatiotemporal model to map soil organic matter (SOM) content.•The model was conveniently temporally transferred to predict SOM content of 1986–2007.•The model had a better accuracy than another one in a previous study.